Nursing care in the surgical setting: analysis of a situation (2020)
Objective: To analyze a nursing situation in the surgical environment in the light of the knowledge patterns of Carper, Chinn and Kramer, contextualization of the situation in the world views of reality, to contribute to the premise that care situations strengthen nursing theory and care from an epistemological perspective. Methods: analysis of the situation based on current knowledge patterns. Conclusion: Nursing knowledge patterns, as well as visions of the world of reality, allow nursing professionals to give a theoretical and epistemological support to care as the essence of the profession.